Considering Psychosocial Factors When Investigating Blood Pressure in Patients with Short Sleep Duration: A Propensity Score Matched Analysis - Ningjing Qian; Dandan Yang; Huajun Li; Siyin Ding; Xia Yu; Qingqiu Fan; Zhebin Yu; Shenfeng Ye; Hualiang Yu; Yaping Wang; Xiaohong Pan (International Journal of Hypertension)
Few studies have considered psychosocial characteristics when investigating the associations between sleep duration and blood pressure (BP). In this study, we took propensity score matching (PSM) to adjust for psychosocial characteristics when comparing BP between individuals with short sleep duration and those with normal sleep duration. A total of 429 participants were included. 72 participants with sleep duration ≤6 h and 65 participants with sleep duration >6 h were matched after PSM. We compared office BP, 24-hour BP, and prevalence of hypertension in the populations before and after PSM, respectively. In the unmatched population, participants with sleep duration ≤6 h were observed with higher office diastolic BP (DBP) and 24-h systolic BP (SBP)/DBP (all P<0.05). In the matched populations, the differences between the two groups (sleep duration ≤6 h vs. sleep duration >6 h) in office DBP (88.4 ± 10.9 vs. 82.5 ± 11.1 mm Hg; P=0.002), 24-h SBP (134.7 ± 12.0 vs. 129.3 ± 11.6 mm Hg; P=0.009), and 24-h DBP (83.4 ± 9.9 vs. 78.1 ± 10.1 mm Hg; P=0.002) become more significant. Participants with sleep duration ≤6 h only show higher prevalence of hypertension based on 24-h BP data, while analysis after PSM further revealed that these with sleep duration ≤6 h presented about 20% higher prevalence of elevated BP up to office diagnosed hypertension threshold. Therefore, psychosocial characteristics accompanied with short sleep duration should be fully valued in individuals at risks for elevated BP. This trial is registered with NCT03866226.